2019
DOI: 10.3389/fimmu.2019.01591
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoids Shape Macrophage Phenotype for Tissue Repair

Abstract: Inflammation is a complex process which is highly conserved among species. Inflammation occurs in response to injury, infection, and cancer, as an allostatic mechanism to return the tissue and to return the organism back to health and homeostasis. Excessive, or chronic inflammation is associated with numerous diseases, and thus strategies to combat run-away inflammation is required. Anti-inflammatory drugs were therefore developed to switch inflammation off. However, the inflammatory response may be beneficial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 151 publications
(192 reference statements)
7
67
0
Order By: Relevance
“…(27,29,35,67,82)), we demonstrate that inflammation and MΦs/µglia are required for RPE regeneration in vivo. Synthetic GCs, such as dexamethasone, have been widely used to suppress inflammation and do so by attenuating the inflammatory phase post-injury and driving macrophages toward an anti-inflammatory phenotype (87)(88)(89). Results from our study support the existence of a critical inflammatory phase during RPE regeneration, as evidenced by expression of phagocytic (e.g.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…(27,29,35,67,82)), we demonstrate that inflammation and MΦs/µglia are required for RPE regeneration in vivo. Synthetic GCs, such as dexamethasone, have been widely used to suppress inflammation and do so by attenuating the inflammatory phase post-injury and driving macrophages toward an anti-inflammatory phenotype (87)(88)(89). Results from our study support the existence of a critical inflammatory phase during RPE regeneration, as evidenced by expression of phagocytic (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…Several phases have been characterized following tissue injury: I) the inflammatory phase, in which leukocytes are recruited, secrete pro-inflammatory cytokines, and begin phagocytosis; II) the resolution phase, in which macrophages continue to phagocytose cell debris and make the switch from a pro-to an anti-inflammatory phenotype; and III) the regeneration phase, in which injured tissues initiate proliferation (82,87). Indeed, sequential progression of resolution and regeneration phases have been shown post-tail fin resection in zebrafish (82).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to study whether GR Lysmcre mice are also sensitized in bacterial sepsis models such as the CLP model and, if so, whether this could be linked to an increased bacterial burden along with increased inflammation. Next to enhancing phagocytosis of bacteria, GCs also enhance the clearance of apoptotic cells and cell debris, i.e., efferocytosis, which is important to start tissue repair [see recent review on this topic; ( 56 )]. A possible mechanism explaining the apparently opposing effects of GCs in sepsis is by a GC-induced differentiation of a specific anti-inflammatory subtype of monocytes, which seems to be actively involved in resolution of inflammatory reactions instead of a global suppression of monocytic effector functions as was originally thought ( 57 ).…”
Section: Role Of Endogenous Gcs In Sepsismentioning
confidence: 99%
“…Moreover, at low, physiological doses, GCs have been shown to dampen the systemic inflammatory response, while preserving innate immunity [11]. Several studies showed that dexamethasone, a typical GR ligand, increases the phagocytic activity of monocytes and macrophages using a variety of particles (zymosan, heat-killed yeast, apoptotic neutrophils, latex beads, bacteria) [13].…”
mentioning
confidence: 99%